PENGARUH INDIKATOR MAKRO DAN HARGA EMAS DUNIA TERHADAP INDEKS HARGA SAHAM SYARIAH (JAKARTA ISLAMIC INDEX) - Ari Agestiani; Himawan Arif Sutanto (ECONBANK: Journal of Economics and Banking, 2019)
This study aims to determine macroeconomic factors such as interest rates, inflation, exchange rates, gross domestic product, and world gold prices in the Jakarta Islamic Index. This study uses time series data for 2015-2017. The data analysis technique used in this study is Multiple Linear Regression. The results of the study show that interest rates and exchange rates have negative effect on the Jakarta Islamic Index. While the world gold price looks positiveeffect towards the Jakarta Islamic Index. Meanwhile, the GDP does not oppose the Jakarta Islamic Index. R2adj value of 0.781 which shows the variation of the Jakarta Islamic Index can explain the factors of interest rates, exchange rates, world gold prices, the exchange rate and GDP of 78.1%. For investors who want to invest their capital in Indonesia, pay more attention to macro economic factors and approve selected instruments based on sharia, the main sharia capital market can make JII as a reference